Using Rhetorical Situations to Examine and Improve Vaccination Communication - Ihlen, Øyvind; Toledano, Margalit; Just, Sine Nørholm (Frontiers in Communication, 2021)
Opinion polls have documented a considerable public skepticism towards a COVID-19 vaccine. Seeking to address the vaccine skepticism challenge this essay surveys the research on vaccine hesitancy and trust building through the lens of the rhetorical situation and points towards five broad principles for a content strategy for public health communicators in regards to vaccination: (1) vaccine hesitancy is not irrational per se; (2) messages should be tailored to the various hesitancy drivers; (3) what is perceived as trustworthy is situational and constantly negotiated; (4) in areas of uncertainty where no exact knowledge exists, the character of the speaker becomes more important; and (5) the trustworthiness of the speaker can be strengthened through finding some common ground – such as shared feelings or accepted premises – with the audience. Such common insights are on offer in the literature on rhetoric and persuasion and linked here with the research on vaccine communication and trust focusing specifically on the latter and character.